The Meromorphic Solutions of the Zakharov-Kuznetsov Modified Equal Width Equation (Analysis in Theory and Applications, 2017)
In this paper, we use the complex method to obtain all meromorphic solutions of the complex Zakharov-Kuznetsov modified equal width equation, then findthe exact traveling wave solutions of the Zakharov-Kuznetsov modified equal widthequation. At last, we give some computer simulations to illustrate our main results.